This is just a function of v. All you need to think of is plugging (w + 3) into your function. You can picture it like this: pretend that w + 3 is a certain number like "a" for example. So your question becomes this:
v(w + 3) = v(a)
So
v(w) = 2w - 1
v(a) = 2a - 1
But a = w + 3 so substitute that back in.
v(w + 3) = 2(w + 3) - 1
And expand and simplify
v(w + 3) = 2w + 6 - 1
v(w + 3) = 2w + 5
And this is your answer.
Another way to say this is that you are replacing your original "w" with "w + 3" now.
v(w) = 2w - 1
v(w + 3) = 2(w + 3) - 1
v(w + 3) = 2w + 6 - 1
v(w + 3) = 2w + 5
And you will get the same answer.